Establishing winter annual cover crops by interseeding into Maize and Soybean. (6th February 2020) - Mohammed, Yesuf Assen; Matthees, Heather L.; Gesch, Russ W.; Patel, Swetabh; Forcella, Frank; Aasand, Kyle; Steffl, Nicholas; Johnson, Burton L.; Wells, M. Scott; Lenssen, Andrew W.
Abstract: The limited time available for cover crop establishment after maize ( Zea mays L.) and soybean [ Glycine max (L.) Merr.] harvest is one of the main reasons for low cover crop adoption in the upper Midwest. Therefore, a 2‐yr multilocation study was conducted to evaluate winter annual cover crops establishment, their effect on main crop grain yields, and soil water content when interseeded into standing maize and soybean. Treatments were three interseeding dates (broadcasting at R4, R5, and R6 growth stages for maize, and R6, R7, and R8 for soybean) and three cover crops (winter camelina [WC] [ Camelina sativa L.], field pennycress [PC] [ Thlaspi arvense L.], winter rye [ Secale cereale L.] plus a no cover crop control). Cover crop establishment and growth varied with interseeding date across locations and seasons for both maize and soybean systems. Averaged over the years, rye produced more green cover and biomass than the oilseeds in spring. However, at the northern‐most site, the greatest (40%) green cover was recorded from pennycress and indicates its potential as a cover crop. Seeding date and cover crops did not negatively affect maize or soybean grain yields or soil water content. Generally, cover crop establishment and growth were better in the soybean system than maize due to better light penetration. Further research is needed to develop better suited cultivars and/or agronomic management practices for interseeding into maize. The results of this study indicate that producers could integrate these covers to diversify and add ecosystem services to soybean production practices.